Development of sin as personal and social: a critical comparison of Irenaeus of Lyons, Martin Luther and Juan Luis Segundo - Mentoor, P M (Department of Religious Studies, 2015)
This thesis explores the development of the Doctrine of Sin as personal and social in the thinking of three representative theologians, Irenaeus, Martin Luther and Juan Luis Segundo. We shall show that both their understanding of sin, and their understanding of redemption is at once personal and social. This thesis rejects any individualistic or private conception of sin as unbiblical and contrary to the mainstream of Christian tradition. We shall show how the three theologians we have chosen expose the corporate nature of sin, and therefore show an awareness of a deeper, communal involvement of human persons in sin, thus demonstrating that sin is both personal and social. At the same time each of the theologians approaches the problem in a different way, highlighting that dimension of sin which is most appropriate in his particular context.